2011
DOI: 10.1002/lary.22366
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disease and compressive symptoms

Abstract: Patients with thyroid disease frequently present with compressive symptoms, and the majority of patients experience relief postoperatively. The volume of the thyroid gland is associated with compressive symptoms along with additional contributing factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 12 publications
2
41
0
4
Order By: Relevance
“…They are reported as generic discomfort, tightness, lump, foreign body, difficulty or pain during swallowing and are often slight [2]. These are frequently complained by patients with thyroid diseases and considered a possible indication to surgery apart from thyroidectomy [3,4]. Otherwise, they can persist or appear after the thyroidectomy in the presence of complications, such as a laryngeal nerve damage (superior laryngeal nerve -SLN, or inferior laryngeal nerve -RLN) as well as after a thyroidectomy in which a postoperative SLN and/or a RLN damage can be excluded by means of an ORL evaluation performed just after the thyroidectomy [2,5e7].…”
Section: Introductionmentioning
confidence: 99%
“…They are reported as generic discomfort, tightness, lump, foreign body, difficulty or pain during swallowing and are often slight [2]. These are frequently complained by patients with thyroid diseases and considered a possible indication to surgery apart from thyroidectomy [3,4]. Otherwise, they can persist or appear after the thyroidectomy in the presence of complications, such as a laryngeal nerve damage (superior laryngeal nerve -SLN, or inferior laryngeal nerve -RLN) as well as after a thyroidectomy in which a postoperative SLN and/or a RLN damage can be excluded by means of an ORL evaluation performed just after the thyroidectomy [2,5e7].…”
Section: Introductionmentioning
confidence: 99%
“…But, in Speech-Language clinic practice, before the surgery procedure, is already observed the diseases associated to thyroid causing complaints of voice of endocrine etiology 1,4,5 . These complaints are due to several factors: for instance, in hypothyroidism the increase of hyaluronic acid in vocal folds lamina propria may lead to fluid retention and thickening of vocal folds 6 ; in hyperthyroidism the results are believed to be resultant of the decrease in sub-glottic pressure caused by the weakness of breathing muscles, 7 and in diseases with the abnormal growth of thyroid the dysphonia may be caused by pressing the larynx nerve 8,9 . Some researches were already developed to evaluate the voice disorders faced by adult patients with thyroid disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The auditory-perceptual did not capture this difference, probably due to the fact of specialist analysis is only focused on noise emission in this moment; for this reason, it does not allow achieving other dimensions which only the patient assessed can access. It is worth to mention that patients with thyroid diseases frequently show compressive complaints in cervical region 4 , and these symptoms associated to the disease may influence the worsening of the voice self-assessment. In addition, in a prior research 20 with a similar population, it was found that the worsening of vocal self-assessment is correlated to the increase of voice negative impact in the quality of life, which stresses the fact of other factors besides the vocal signal deviated contribute to the perception that the individual has about his own voice.…”
Section: Resultsmentioning
confidence: 99%